2018
DOI: 10.1111/acel.12747
|View full text |Cite
|
Sign up to set email alerts
|

Increasing autophagy and blocking Nrf2 suppress laminopathy‐induced age‐dependent cardiac dysfunction and shortened lifespan

Abstract: SummaryMutations in the human LMNA gene cause a collection of diseases known as laminopathies. These include myocardial diseases that exhibit age‐dependent penetrance of dysrhythmias and heart failure. The LMNA gene encodes A‐type lamins, intermediate filaments that support nuclear structure and organize the genome. Mechanisms by which mutant lamins cause age‐dependent heart defects are not well understood. To address this issue, we modeled human disease‐causing mutations in the Drosophila melanogaster Lamin C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 48 publications
6
30
0
Order By: Relevance
“…Cardiac dysfunction was associated with nuclear enrichment of Cap and collar C (CncC) [the orthologue of mammalian nuclear erythroid 2-related factor 2 (Nrf2)], suggesting cellular redox imbalance in flies with Lamin C mutations. Upregulating autophagy by Atg1 overexpression in this model attenuated cytoplasmic Lamin C accumulation, improved nuclear morphology, promoted myofibrillar organization, and ameliorated cardiac dysfunction [92]. Overall, this study demonstrated that upregulating autophagy improved the clearance capacity of cardiac cells to an extent that restored cardiac function.…”
Section: Autophagy Suppression In Cardiac Agingmentioning
confidence: 52%
See 1 more Smart Citation
“…Cardiac dysfunction was associated with nuclear enrichment of Cap and collar C (CncC) [the orthologue of mammalian nuclear erythroid 2-related factor 2 (Nrf2)], suggesting cellular redox imbalance in flies with Lamin C mutations. Upregulating autophagy by Atg1 overexpression in this model attenuated cytoplasmic Lamin C accumulation, improved nuclear morphology, promoted myofibrillar organization, and ameliorated cardiac dysfunction [92]. Overall, this study demonstrated that upregulating autophagy improved the clearance capacity of cardiac cells to an extent that restored cardiac function.…”
Section: Autophagy Suppression In Cardiac Agingmentioning
confidence: 52%
“…Of particular relevance to this review, a common manifestation of Lamin A/C mutations and the subsequent accumulation of progerin caused cardiac dysfunction manifested by atrial arrhythmia and hypertrophic cardiomyopathy [90,91]. Evidence supporting this link is provided by a fly model of cardiolaminopathy exhibiting repressed autophagy, accumulation of cytoplasmic Lamin C aggregates, impaired cardiac function, severe myofibrillar degeneration, nuclear morphological defects, and evidence of oxidative stress [92]. Cardiac dysfunction was associated with nuclear enrichment of Cap and collar C (CncC) [the orthologue of mammalian nuclear erythroid 2-related factor 2 (Nrf2)], suggesting cellular redox imbalance in flies with Lamin C mutations.…”
Section: Autophagy Suppression In Cardiac Agingmentioning
confidence: 98%
“…Collectively, our findings suggest that autophagy impairment switches on Nrf2-mediated cardiac pathological remodeling and dysfunction. Interestingly, Bhide et al (2018) documented that in a Drosophila model of laminopathy, laminopathy-associated age-dependent cardiac dysfunction, could be rescued by knockdown of Nrf2, or enhancement of autophagy in the heart. These findings suggest that age-dependent autophagy deficiency may turn on Nrf2-mediated cardiac dysfunction in the Drosophila model of laminopathy.…”
Section: Nrf2-mediated Cardiac Damagementioning
confidence: 99%
“…RNAi-mediated knockdown of PINK1 remarkably rescued CHCHD10 S59L -induced mitochondrial morphologic and functional defects in HeLa cells ( (45,46). However, strong mitochondrial abnormalities in PRKN-deficient HeLa cells indicate the presence of parkin-independent toxic mechanisms.…”
Section: Pink1/parkin Mediates Dominant Toxicity In Hela Cellsmentioning
confidence: 96%